2018
DOI: 10.1108/bij-06-2015-0059
|View full text |Cite
|
Sign up to set email alerts
|

Cluster strategy and supply chain management

Abstract: Purpose The purpose of this paper is to highlight the characteristic role of specialized markets and traders in the internationalization of emerging economies by examining the linkages between supply chain management (SCM) and industrial clustering in China. Design/methodology/approach Multi-method approach was employed as primary data were collected from a case study of Shaoxing textile cluster, and was supplemented with secondary data to triangulate the findings. The proposition that competitive advantages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Literature suggests substantial association between organizational culture's ambidexterity and innovation consequence [17,25]. Researchers found that culture in which knowledge is highly share has significantly impacted ambidexterity and strategic leadership helped in achieving this culture.…”
Section: New Product Innovation Outcomes and Ambidextrous Organizatiomentioning
confidence: 99%
See 1 more Smart Citation
“…Literature suggests substantial association between organizational culture's ambidexterity and innovation consequence [17,25]. Researchers found that culture in which knowledge is highly share has significantly impacted ambidexterity and strategic leadership helped in achieving this culture.…”
Section: New Product Innovation Outcomes and Ambidextrous Organizatiomentioning
confidence: 99%
“…The pursuance of innovation helps in attaining competitive advantages and realizing superior performance in competitive market environments, nonetheless efficacious innovations remain challenging task for enterprises. Recent studies reveal the importance of both technology-related innovations, which refers to the adoption of disruptive technologies in new product development processes [23,25]. Innovation also depends on exploration and exploitation processes, and balancing exploration and exploitation offers another difficult dilemma.…”
Section: New Product Innovation Outcomes and Ambidextrous Organizatiomentioning
confidence: 99%
“…SEZs, by definition, are (i) a geographically demarcated area, (ii) having single administration, (iii) providing tax benefits, (iv) providing ease of processes and customs, (v) providing more liberal policy and juridical regime than rest of the country [9]. Such zones help in catapulting new technologies, catalyze economic development by export orientation, and upgrade and optimally utilize the existing infrastructure of a particular region [3,4,8,24,25] that otherwise normally faces hindrances in doing so [6,26]. There are many types of SEZs based on their objectivity and operations.…”
Section: Key Factors Of Sezsmentioning
confidence: 99%
“…The advantages of natural resources are easier for the market to specialize in the commodities they sell and build a kind of special cluster to increase the efficiency of their supply chain. (Ikram et al 2018).…”
Section: Specializing Commoditiesmentioning
confidence: 99%